2018
DOI: 10.1093/hmg/ddy327
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genome-wide association studies for body fat distribution in 694 649 individuals of European ancestry

Abstract: One in four adults worldwide are either overweight or obese. Epidemiological studies indicate that the location and distribution of excess fat, rather than general adiposity, is most informative for predicting risk of obesity sequellae, including cardiometabolic disease and cancer. We performed a genome-wide association study meta-analysis of body fat distribution, measured by waist-to-hip ratio adjusted for BMI (WHRadjBMI), and identified 463 signals in 346 loci. Heritability and variant effects were generall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
987
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 885 publications
(1,100 citation statements)
references
References 35 publications
22
987
2
3
Order By: Relevance
“…Of the 16 suggestive SNPs associated with WHtR, variants in or near LTBP1, PDE1C, GALNT17, DPP6, MAP4K5 and EYA2 were nominally associated with BMI or WHR in adult population 17,18,35,36 ( 37 In the present study we utilized Metabochip, a custom genotyping chip for fine-mapping and replication, which includes altogether 200 000 SNPs from loci that were associated, or were promising for several complex metabolic traits for example, type 2 diabetes, cardiovascular diseases, and their key risk factors: BMI, blood glucose, insulin land lipid concentrations and blood pressure back in 2012. 38 We created BMI-GRSs based on data of Speliotes et al, 17 and 30 of these 32 SNPs were incorporated in Metabochip.…”
Section: Top Snps Related To Bmi Z-score and Waist-toheight Ratio Imentioning
confidence: 99%
“…Of the 16 suggestive SNPs associated with WHtR, variants in or near LTBP1, PDE1C, GALNT17, DPP6, MAP4K5 and EYA2 were nominally associated with BMI or WHR in adult population 17,18,35,36 ( 37 In the present study we utilized Metabochip, a custom genotyping chip for fine-mapping and replication, which includes altogether 200 000 SNPs from loci that were associated, or were promising for several complex metabolic traits for example, type 2 diabetes, cardiovascular diseases, and their key risk factors: BMI, blood glucose, insulin land lipid concentrations and blood pressure back in 2012. 38 We created BMI-GRSs based on data of Speliotes et al, 17 and 30 of these 32 SNPs were incorporated in Metabochip.…”
Section: Top Snps Related To Bmi Z-score and Waist-toheight Ratio Imentioning
confidence: 99%
“…The index SNPs were expanded to give proxy SNPs in high LD (r 2 ≥ 0.8), and the sets of index and proxy SNPs were combined (index/proxy SNPs; Supplementary Material, Table S4). We separately collected sets of imputed SNPs (p < 6.6 x 10 -9 ) at this locus obtained from summary statistics from one WHRadjBMI meta-analysis of 694,649 individuals (38) and from an eBMD meta-analysis of 426,824 individuals (27) (Supplementary Material, Table S5).…”
Section: Tbx15 Enhancer or Promoter Chromatinmentioning
confidence: 99%
“…There are two obesity missense variants in TBX15, namely, rs10494217 (G/T, 0.84/0.16; H156N) in exon 3 and rs61730011 (A/C, 0.96/0.04; M566R) in exon 8 ( Fig. 1B, double arrows) (13,38,40). The meta-analysis by Justice et al (13) involving 476,546 individuals (88% EUR) found a highly significant association of both rs10494217 (p = 2 x 10 -14 ) and rs61730011 (p = 3 x 10 -21 ) with WHRadjBMI, and similar results were obtained for the former SNP in the study of Pullit et al (38) Table S5).…”
Section: Obesity-related Non-synonymous Codon Variants In Tbx15 Exonsmentioning
confidence: 99%
See 2 more Smart Citations